PENGARUH EKONOMI EKSTERNAL DAN INTERNAL TERHADAP TABUNGAN DI NEGARA-NEGARA MAJU DI EROPA - Wulandari, Agatha Ellesonia (Journal of Financial Economics & Investment, 2024)
Savings are very important because they can provide financial security by setting aside a portion of income, so that you have reserve funds for urgent or future needs, and can overcome unexpected financial situations and provide long-term financial freedom. There are two factors influence savings, namely internal factors include economic growth and general government debt, while external factors include fuel imports and foreign direct investment. The aim of this research is to determine the impact of the external and internal economy on savings in developed countries with the highest economic growth rates in Europe. The data analysis technique used is panel regression. The research results show that economic growth has a positive effect on savings, while imports of steel materials and direct investment have a negative effect on savings. Only the general government debt variable has a negative and insignificant effect on savings in developed European countries, including Germany, Italy, Spain, the Netherlands, Switzerland.